Bending behaviour of ferrocement slab including basalt fibre in high strength cement matrix. (2021) - Deepak, M.S.; Surendar, M.; Aishwarya, B.; Beulah Gnana Ananthi, G.
Abstract: Ferrocement is the term given to a composite member made of cementitious-based mortar with orderly spaced less diameter thick steel wire weld-mesh. In the present study, ferrocement slabs subjected to bending under four-point loading and impact using a drop weight loads were investigated. High Strength Cement (HSC) mortar mixes were designed, developed and selected for casting the ferrocement slab specimens. The slab has been casted using square wire weld mesh of opening size 50 mm × 50 mm and 10 mm thick was used as reinforcement along with varying percentage of basalt fibre 1%, 2% incorporations. It was found that the basalt fibres inclusion improvised the flexural strength and energy absorption capacity. It was also found that increased number of mesh layers also improvised the strength of the ferrocement member.